MEDIA AUDIOVISUAL DAN PICTURE AND PICTURE TENTANG MENYAMBUNG HURUF HIJAIYAH DAPAT MENINGKATKAN BACAAN AL QUR™AN DAN BAHASA ARAB SISWA KELAS I MADRASAH IBTIDAIYAH NEGERI 7 LANGKAT BOHOROK - Nurâ€™Aini, Nurâ€™Aini (JGK (Jurnal Guru Kita), 2022)
Abstract: Audiovisual and Picture and Picture Media About Connecting Hijaiyah Letters Can Improve Al-Qur’an and Arabic Reading of First Grade Students of Madrasah Ibtidaiyah Negeri 7 Langkat Bohorok. Education is a process of guidance or learning given by adults to children who are developing. In the learning process it is very important to improve the quality of learning, therefore it takes a variety of learning media, so that teachers can create a supportive learning atmosphere so that learning objectives are achieved. The researcher (class teacher) tried to use Audiovisual Media and Picture And Picture about connecting Hijaiyah letters in order to improve the reading of the Qur’an and Arabic for Class I students of Madrasah Ibtidaiyah Negeri 7 Langkat Bohorok. The results obtained in the first cycle an average of 73%, the second cycle an average of 78%, the third cycle an average of 83%, there is an average increase, although only 83% on average at the end of the success, meaning the use of Audiovisual and Picture Media And Picture can be used in the teaching and learning process (KBM) in the classroom for certain certain subject matter.